Does contact improve attitudes towards migrants in China?1: Evidence from urban residents. Issue 2 (5th February 2018) - Xue, Sen
Abstract: Over the past three decades, China has experienced significant internal migration. However, migrants are often socially segregated and discriminated against in their destination cities in China. This paper uses a large representative survey to investigate whether interpersonal contact between urban locals and migrants improves urban locals' attitudes towards migrants. The novel part of this paper is to examine the effect of different contact experiences on multiple dimensions of attitudes. The results show distinct patterns between the effects of non‐intimate and intimate contact experiences. All the OLS results, IV results and IV results together with Lewbel's (2012 ) heteroscedasticity identification approach suggest that non‐intimate contact experience only significantly improves willingness to engage in non‐intimate interactions, and the magnitude of the effect reduces as the intimacy level of the intended interaction increases. On the contrary, intimate contact experience significantly improves willingness to engage in both non‐intimate and intimate interactions.